Relationship between craniofacial skeletal patterns and anatomic characteristics of masticatory muscles: a systematic review and meta-analysis - David Togninalli; Gregory S. Antonarakis; Alexandra K. Papadopoulou (SpringerOpen, 2024)
Abstract Background The anatomic characteristics of the masticatory muscles differ across craniofacial skeletal patterns. Objective To identify differences in the anatomic characteristics of masticatory muscles across different sagittal and vertical craniofacial skeletal patterns. Eligibility criteria Studies measuring the thickness, width, cross-sectional area (CSA), volume and orientation of masticatory muscles in healthy patients of different sagittal (Class I, Class II, and Class III) and/or vertical (normodivergent, hypodivergent, and hyperdivergent) patterns. Information sources Unrestricted literature searches in 8 electronic databases/registers until December 2023. Risk of bias and synthesis of results Study selection, data extraction, and risk of bias assessment with a customised tool were performed independently in duplicate. Random-effects meta-analysis and assessment of the certainty of clinical recommendations with the GRADE approach were conducted. Results 34 studies (37 publications) were selected with a total of 2047 participants and data from 16 studies were pulled in the meta-analysis. Masseter muscle thickness in relaxation was significantly greater by 1.14 mm (95% CI 0.74-1.53 mm) in hypodivergent compared to normodivergent patients while it was significantly decreased in hyperdivergent patients by − 1.14 mm (95% CI − 1.56 to − 0.73 mm) and − 2.28 mm (95% CI − 2.71 to − 1.85 mm) compared to normodivergent and hypodivergent patients respectively. Similar significant differences were seen between these groups in masseter muscle thickness during contraction as well as masseter muscle CSA and volume. Meta-analyses could not be performed for sagittal categorizations due to insufficient number of studies. Conclusions Considerable differences in masseter muscle thickness, CSA and volume were found across vertical skeletal configurations being significantly reduced in hyperdivergent patients; however, results should be interpreted with caution due to the high risk of bias of the included studies. These variations in the anatomic characteristics of masticatory muscles among different craniofacial patterns could be part of the orthodontic diagnosis and treatment planning process. Registration: PROSPERO CRD42022371187 .